Genetic Polymorphisms Associated with Perioperative Joint Infection following Total Joint Arthroplasty: A Systematic Review and Meta-Analysis - Adel Hijazi; Ahmad Hasan; Adam Pearl; Ramiz Memon; Michael Debeau; Mariana Roldan; Mohamed E. Awad; Ehsen Abdul-Kabir; Khaled J. Saleh (MDPI AG, 2022)
The number of orthopedic procedures, especially prosthesis implantation, continues to increase annually, making it imperative to understand the risks of perioperative complications. These risks include a variety of patient-specific factors, including genetic profiles. This review assessed the current literature for associations between patient-specific genetic risk factors and perioperative infection. The PRISMA guidelines were used to conduct a literature review using the PubMed and Cochrane databases. Following title and abstract review and full-text screening, eight articles remained to be reviewed-all of which compared single nucleotide polymorphisms (SNPs) to periprosthetic joint infection (PJI) in total joint arthroplasty (TJA). The following cytokine-related genes were found to have polymorphisms associated with PJI: TNFα (p < 0.006), IL-6 (p < 0.035), GCSF3R (p < 0.02), IL-1 RN-VNTR (p = 0.002), and IL-1B (p = 0.037). Protein- and enzyme-related genes that were found to be associated with PJI included: MBL (p < 0.01, p < 0.05) and MBL2 (p < 0.01, p < 0.016). The only receptor-related gene found to be associated with PJI was VDR (p < 0.007, p < 0.028). This review compiled a variety of genetic polymorphisms that were associated with periprosthetic joint infections. However, the power of these studies is low. More research must be conducted to further understand the genetic risk factors for this serious outcome.